What's in that egg? : a book about life cycles - Baines, Rebecca (Washington, D.C. : National Geographic, 2009)
An introduction to eggs that discusses the development of a chick embryo and describes the variety of egg shapes and colors.
"A Zigzag Book"--Cover p. [4].
"National Geographic Kids"--Cover.
2.3
K-3
Keywords: Eggs -- Juvenile literature; Embryology -- Juvenile literature; Eggs; Embryology; Eggs; Embryology